Analisis Kinerja Ekonomi Makro dan Kinerja Perbankan Terhadap Stabilitas Perbankan Bank Umum Syariah di Indonesia: Sebuah Studi Empiris : Bank Panin Dubai Syariah dan Bank Aceh Syariah - Rizki Rizki; Bakhtiar Efendi; Lia Nazliana Nasution (Jurnal Riset Ekonomi dan Akuntansi, 2025)
The purpose of this study is to ascertain how banking and macroeconomic performance affect Indonesia's Sharia Commercial Banks' stability. Panel Regression is the technique employed. GDP, inflation, BI-Rate, ROA, CAR, assets, and BOPO are the independent variables that are used. Z-Score is utilized as the dependant variable in the meantime. The World Bank, Bank Indonesia, and financial records from Bank Aceh Syariah and Bank Panin Dubai were the sources of the data. The data used spans the years 2011 through 2024. The findings indicate that the Z-Score is positively impacted by GDP, inflation, BOPO, ROA, and CAR. In the meantime, Z-Score is negatively impacted by assets and BI-Rate.